From norm to reality: The BNCC and the need for contextualized education in the Brazilian Amazon (Research, Society and Development, 2025)
This bibliographic study aims to critically reflect on the National Common Curricular Base (BNCC) as a normative document that guides Basic Education in Brazil, especially in contexts of symbolic and geographic exclusion, such as the countryside of the state of Amazonas. To this end, it articulates curricular concepts presented by authors such as Sacristán and Moran, along with statistical data and reports on the challenges faced by teachers and students in riverside and isolated regions. Although the BNCC proposes equity and diversity, it presents structural and cultural limitations when applied to contexts with limited access to technology, infrastructure, and teacher training. The standardization of the curriculum often overlooks local sociocultural specificities, which compromises the effectiveness of the teaching and learning process. This paper advocates for flexible and intercultural curricula, with methodologies adapted to regional realities and investment in contextualized teacher education. It also proposes accessible alternatives for technological and curricular integration, aiming to overcome educational inequalities and promote a more inclusive education in the Amazonian countryside.